Rare ovarian lesion in an adolescent girl - Ramasamy Senthilnathan; Paramasivam Jeyakumar; Janardhanam Krishnamohan (Wolters Kluwer Medknow Publications, 2008)
Large solid ovarian lesions are considered malignant in nature in pediatric and adolescent age group. We present an adolescent girl who had large solid ovarian lesion, with negative tumor markers. She underwent laparotomy and right oopherectomy. Histopathology revealed that the lesion was massive ovarian edema. This is an extremely rare lesion of ovary and is benign in nature. Very few case reports are available in English literature. Hence we suggest that massive ovarian edema should be considred as one of the differential diagnosis in all the patients having large solid ovarian lesions with ngative tumor marker assay. Ovarian preservation with the help of frozen section analysis should always be considred in these patients.